1997
DOI: 10.1006/jeem.1997.0998
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Income Elasticities of Demand and Willingness to Pay

Abstract: The relationship between income and willingness to pay for a collectively-provided public good is investigated. We show that while the income elasticity of willingness to pay and the ordinary income elasticity of demand are functionally related, knowledge of one is insufficient to determine the magnitude or even the sign of the other. This is because the sign and magnituJe of the income elasticity of willingness to pay is influenced by a number of other factors which are usually unobservable. Examples are prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(93 citation statements)
references
References 15 publications
8
81
1
3
Order By: Relevance
“…If we assume that WTP is an adequate proxy for quantity demanded, then this finding suggests that water quality is either a normal or luxury good (see, e.g., [90]). The negative slope associated with SOUTH signifies that individuals in the southern region of the US have a lower average WTP (after accounting for other factors like income) to protect water quality compared to other regions ( Table 3).…”
Section: Systematic Variation In Income and Site Variablesmentioning
confidence: 99%
“…If we assume that WTP is an adequate proxy for quantity demanded, then this finding suggests that water quality is either a normal or luxury good (see, e.g., [90]). The negative slope associated with SOUTH signifies that individuals in the southern region of the US have a lower average WTP (after accounting for other factors like income) to protect water quality compared to other regions ( Table 3).…”
Section: Systematic Variation In Income and Site Variablesmentioning
confidence: 99%
“…Hence ε W will be significantly greater than one in the short run and, arguably, smaller in the long run as price elasticities rise. Flores and Carson (1997) show that the size of ε W cannot be determined from the size of ε Y (as is clear from the equation above) and offer no empirical support for small or large values. Kristrom and Riera (1996) analyse contingent valuation studies of environmental change 12 and conclude that ε W is less than one, i.e.…”
mentioning
confidence: 93%
“…Essentially, public goods are exogenous to household and corporate decisions. Hence the relevant income elasticity is what has been called in the literature the 'price flexibility of income' (Randall and Stoll, 1980) or the 'income elasticity of virtual price' (Hanemann, 1991), the 'income elasticity of willingness to pay' (Flores and Carson, 1997), the 'income elasticity of environmental value' and the 'income elasticity of environmental improvement' (Kristrom and Riera, 1996). Appendix E sets out the basic relationships.…”
mentioning
confidence: 99%
“…Ebert (2003), following up on previous work by Aaron and McGuire (1970), Kovenock and Sadka (1981), Kriström and Riera (1996), Flores and Carson (1997), has scrutinized the incidence of environmental benefits and has shown that the income elasticity of WTP for an environmental public good has an inverse relationship to the elasticity of substitution between a composite consumption good and the environmental good in question, assuming a constant-elasticity-of-substitution (CES) utility function. Hence, the income elastic-ity of WTP is smaller (greater) than unity if and only if the environmental good and consumption good are substitutes (complements).…”
Section: Introductionmentioning
confidence: 99%